IoT system testing : an IoT journey from devices to analytics and the edge - Hagar, Jon Duncan (Apress, 2022)
To succeed, teams must assure the quality of IoT systems. The world of technology continually moves from one hot area to another; this book considers the next explosionof IoTfrom a quality testing viewpoint. You'll first gain an introduction to the Internet of Things (IoT), V&V, and testing. Next, you'll be walked through IoT test planning and strategy over the full life cycle, including the impact of data analytics and AI. You will then delve deeper into IoT security testing and various test techniques, patterns, and more. This is followed by a detailed study of IoT software test labs, architecture, environments and AI. There are many options for testing IoT qualities based on the criticality of the software and risks involved; each option has positives, negatives, as well as cost and schedule impacts. The book will guide start-up and experienced teams into these paths and help you to improve the testing and quality assessment of IoT systems. You will: Understand IoT software test architecture and planning Master IoT security testing and test techniques Study IoT test lab automation and architectures Review the need for IoT security, data analytics, AI, Neural Networks and dependability using testing and V&V.